A Cyclin E Centered Genetic Network Contributes to Alcohol-Induced Variation in Drosophila Development. Issue 8 (1st August 2018) - Morozova, Tatiana V; Hussain, Yasmeen; McCoy, Lenovia J; Zhirnov, Eugenea V; Davis, Morgan R; Pray, Victoria A; Lyman, Rachel A; Duncan, Laura H; McMillen, Anna; Jones, Aiden; Mackay, Trudy F C; Anholt, Robert R H
Abstract: Prenatal exposure to ethanol causes a wide range of adverse physiological, behavioral and cognitive consequences. However, identifying allelic variants and genetic networks associated with variation in susceptibility to prenatal alcohol exposure is challenging in human populations, since time and frequency of exposure and effective dose cannot be determined quantitatively and phenotypic manifestations are diverse. Here, we harnessed the power of natural variation in the Drosophila melanogaster Genetic Reference Panel (DGRP) to identify genes and genetic networks associated with variation in sensitivity to developmental alcohol exposure. We measured development time from egg to adult and viability of 201 DGRP lines reared on regular or ethanol- supplemented medium and identified polymorphisms associated with variation in susceptibility to developmental ethanol exposure. We also documented genotype-dependent variation in sensorimotor behavior after developmental exposure to ethanol using the startle response assay in a subset of 39 DGRP lines. Genes associated with development, including development of the nervous system, featured prominently among genes that harbored variants associated with differential sensitivity to developmental ethanol exposure. Many of them have human orthologs and mutational analyses and RNAi targeting functionally validated a high percentage of candidate genes. Analysis of genetic interaction networks identified C yclin E (C ycE ) as a central, highly interconnected hub gene. Cyclin E encodes a protein kinase associated with cell cycle regulation and is prominently expressed in ovaries. Thus, exposure to ethanol during development of Drosophila melanogaster might serve as a genetic model for translational studies on fetal alcohol spectrum disorder.